2004
DOI: 10.1258/1357633041424458
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing in child and adolescent telepsychiatry: a systematic review of the literature

Abstract: A systematic review of child and adolescent telepsychiatry was conducted. It was based on a search of the electronic databases MEDLINE and PsycINFO covering the period 1966 to June 2003. Studies were selected for review if they concerned videoconferencing for patient care or consultation, evaluated a clinical service or education, or assessed satisfaction with videoconferences. Twenty-seven articles were identified that fulfilled the selection criteria. These comprised two reports of randomized controlled expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 25 publications
5
84
1
6
Order By: Relevance
“…Problems relating to audio quality were addressed and improvement was reflected in subsequent evaluations. Reviews on child and adolescent psychiatry studies 40 and adult studies 41 also mentioned the audiovisual quality of the videoconference as one of the drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Problems relating to audio quality were addressed and improvement was reflected in subsequent evaluations. Reviews on child and adolescent psychiatry studies 40 and adult studies 41 also mentioned the audiovisual quality of the videoconference as one of the drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Телепатронаж -телефон, видеоконференц-связь Синхронное телеконсультирование посредством видеоконференц-связи эффективно при-меняется для диагностики, выбора метода лечения и контроля его результативности у паци-ентов с депрессией, анорексией, расстройствами поведения, фобиями, шизофренией, наруше-ниями внимания и гиперактивностью (дети), химической зависимостью 275 . Видеоконференции могут проводиться как между медицинскими работниками, так и по линии «пациент -врач» (с или без участия абонента -врача или медицинской сестры).…”
Section: балльная оценка = (возраст * 02) + 6 (если в анамнезе фибриunclassified
“…In 1950s' Nebraska, twoway closed circuit television was used, mainly in psychiatry (American Academy of Child & There has been a number of detailed reviews of the literature, including a book on telepsychiatry (Monnier 2003;Wootton 2003Wootton , 2006Pesamaa 2004;Leach 2006;Norman 2006;Hailey 2007; American Academy of Child & Adolescent Psychiatry 2008;Millar 2009). One systematic review of 106 studies across the whole of medicine concluded that 'telemedicine is most effective for verbal interactions, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%